FACTORS INFLUENCING INR LEVEL OF PATIENTS RECEIVING WARFARIN IN SAMUI HOSPITAL - Promkong, Jaruwal (Journal of MCU Nakhondhat, 2023)
This cross - sectional analytical study aimed to investigate INR levels and factors associated in patients receiving services at the Warfarin Clinic in Koh Samui Hospital. Data was collected through medical records and interviews using a questionnaire consisting of four parts: 1) general information and information about warfarin medication, 2) Other medications taken concomitantly with Warfarin and medication adherence, 3) Social factors, and 4) Warfarin Knowledge Assessment Questionnaire consisting of 12 items. The questionnaire was validated for content accuracy by experts and tested for reliability using Cronbach's alpha with a reliability coefficient of 0.703. Data analysis was performed using descriptive statistics including percentages, means, standard deviations, and inferential statistics including Chi - square test. The study included a total of 97 patients, with the majority being male (50.5%) and an average age of 61 ± 8.82 years. The INR levels were within the target range in 60.8% of the patients. Smoking and medication adherence were statistically significantly related to INR levels (p - value < 0.05). Other factors such as gender, age, body mass index, comorbidities, concomitant medications, consumption of high vitamin K foods, knowledge about medication, and alcohol consumption were not significantly related to INR levels. Therefore, it is advisable to promote medication adherence and campaign for smoking cessation by leveraging cooperation from healthcare professionals. Additionally, considering individual patient factors when adjusting medication dosages can enhance the effectiveness and safety of using Warfarin. These measures contribute to optimizing treatment outcomes and minimizing potential risks associated with INR fluctuations. In conclusion, this study highlights the importance of addressing factors such as smoking and medication adherence to achieve desirable INR levels in patients receiving Warfarin therapy. Implementing interprofessional collaboration and tailoring treatment based on individual patient characteristics are key strategies to improve the efficacy and safety of Warfarin usage.